Unlocking potential: how project-based learning influences kindergarten motor skills - Anggarda Paramita Muji; Alwen Bentri; Jamaris Jamaris; Rakimahwati Rakimahwati; Abna Hidayati; Darmansyah Darmansyah; Hendra Hidayat (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: various studies have shown that the Project-Based Learning (PBL) has a significant impact on learning across different educational levels. However, there is an empirical gap, particularly regarding the implementation of PBL in early childhood education. Research in this age is still limited, especially in evaluating the impact of PBL on early childhood motor skills.